Agon Lost – or in Disguise? A Commentary - Ballisager Olav (Physical Culture and Sport: Studies and Research, 2019)
Thanks to John W. Loy one of the recurrent themes in Institute of Scandinavian Physical Culture (ISPC) was “agon”. First, I offer some old Nordic examples on games – possibly with an agonal element. Then I focus on moral and character in order to identify some sort or a vestige of agon and revisit physical culture in terms of “idræt”, an old Nordic word for athletics and sport. Finally, I ask if there is – atavistic or not – in the modern world any glimpse of agonal behavior to be found and appreciated within the three realms or categories, which could be pillars of a physical education program: Nature, combat/competition and aesthetics. Would Edmund Hillary, Nelson Mandela and Pussy Riot qualify into a renewed, more general perception of agon?